CGIAR Research Program on Agriculture for Nutrition and Health - Plan of Work and Budget 2019 - CGIAR Research Program on Agriculture for Nutrition and Health (CGIAR Research Program on Agriculture for Nutrition and Health, 2019)
A4NH is led by the International Food Policy Research Institute and managed by six additional partners: Bioversity International, the International Center for Tropical Agriculture, the International Institute of Tropical Agriculture, the International Livestock Research Institute, the London School of Hygiene and Tropical Medicine, and Wageningen University and Research.